Application of Datamining for estimating the marketing success of the women entrepreneurs - Madhavan, Hemalatha; Furzana, Tajvar; Nayaki, Senthil (Journal of Contemporary Research in Management (JCRM), 2014)
Women entrepreneurs incessantly face the problems in marketing their products. In this research study, we examine the marketing problems faced by women entrepreneurs in running their enterprises and designed the marketing strategy for women entrepreneurs in Tamilnadu and also provide suggestions to them how to market their products or services to become successful entrepreneurs. Researcher collected the list of women entrepreneurs in Trichy district and the data was collected through in-depth personal interviews using questionnaire from 291 women entrepreneurs in Tamilnadu. The results of the study have indicated that the women entrepreneurs have to improve their marketing strategies like sales promotion, networking and clustering, brand and technology, visual media advertisement, print media advertisement, distribution channels, direct selling and product variety in their business. And the results of the study have indicated that pricing strategy is not affecting the business success of the women entrepreneurs. These marketing strategies lead to improve the business success of the women entrepreneurs. However the researcher has given some valid suggestions to improve marketing strategies of the women entrepreneurs.